Rancang Bangun Aplikasi Diagnosa Kerusakan Komputer dengan Sistem Pakar Metode Forward Chaining - Susi Widayati; Yudi Irawan Chandra; Raudhatul Zanna Fitriyani (LPPM STIKOM Tunas Bangsa, 2024)
Computers can incur a wide range of damage, varying in severity from minor issues that are easily resolved to more complex problems that might potentially render the computer inoperable. This damage exhibits nearly identical symptoms across many computer components. Unfortunately, computer owners typically overlook these signs, leading to a worsening of the damage and subsequent disruption for computer users. Technicians are highly skilled professionals in the domain of computers. His expertise can be used to a system known as an expert system. The advancement of information technology necessitates innovation in the realm of computer maintenance and identification of hardware malfunctions. The objective of this study is to develop an application that utilizes an Expert System with the Forward Chaining technique to diagnose computer malfunctions. This strategy enables the system to generate diagnostic procedures by utilizing factual information obtained through an interactive exchange with the user. This application is specifically developed to aid users, particularly those with less technical expertise, in discovering and fixing computer issues. The expert system employs artificial intelligence to examine the symptoms provided by the user. It then employs a forward chaining procedure to ascertain the potential harm and the appropriate remedy. The key benefit of this application is its capacity to swiftly and precisely deliver solutions by leveraging the integrated knowledge within the system. The deployment of this application is expected to enhance efficiency in identifying and resolving computer malfunctions, while also offering a superior user experience in managing technical issues on their devices..